TREATMENT OF PATIENTS WITH PANCREATIC NEUROENDOCRINE TUMOURS DEPENDING ON THE DIFFERENTIATION GRADE - A. Z. Isyangulova; R. Sh. Khasanov; R. F. Enikeev; M. G. Gordiev (Сибирский онкологический журнал, 2019)
The incidence of neuroendocrine tumors has significantly increased over the last years.The purpose of the study was to analyze treatment outcomes in patients with pancreatic endocrine tumors (PETs) with regard to histopathologic diagnosis.Material and Methods. The clinical records of 1077 patients with pancreatic tumors were retrospectively analyzed. Fifty patients were diagnosed with PET. Treatment outcomes were assessed with regard to tumor differentiation grade, tumor stage, extent of surgery and drug therapy.Results. The most common histological grade was G1. Patients with G1 tumors had the best 1-and 3-year survival rates regardless of tumor stage. Factors influencing prognosis in patients with PETs were: radical surgery, Ki67 expression level, histological grade (G1–3), tumor stage at diagnosis.